2009
DOI: 10.1073/pnas.0900463106
|View full text |Cite
|
Sign up to set email alerts
|

Signal adaptor DAP10 associates with MDL-1 and triggers osteoclastogenesis in cooperation with DAP12

Abstract: Osteoclasts, cells of myeloid lineage, play a unique role in bone resorption, maintaining skeletal homeostasis in concert with boneproducing osteoblasts. Osteoclast development and maturation (osteoclastogenesis) is driven by receptor activator of NF-B ligand and macrophage-colony stimulating factor and invariably requires a signal initiated by immunoreceptor tyrosine-based activation motif (ITAM)-harboring Fc receptor common ␥ chain or DNAX-activating protein (DAP)12 (also referred to as KARAP or TYROBP) that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 43 publications
1
73
0
Order By: Relevance
“…As expected, DAP12-deficient animals were resistant to lethal shock induced by MDL-1 ( Figure 8A). Another adaptor protein, DAP10, has recently been reported to associate with MDL-1 in osteoclasts and to modulate bone remodeling in concert with DAP12 (30). As shown in Figure 8B, DAP10 -/-mice were also protected, indicating that both DAP12 and DAP10 are important for lethal shock triggered by MDL-1.…”
Section: Activation Of Dap12 Dap10 Syk Pi3k and Akt Is Important mentioning
confidence: 66%
“…As expected, DAP12-deficient animals were resistant to lethal shock induced by MDL-1 ( Figure 8A). Another adaptor protein, DAP10, has recently been reported to associate with MDL-1 in osteoclasts and to modulate bone remodeling in concert with DAP12 (30). As shown in Figure 8B, DAP10 -/-mice were also protected, indicating that both DAP12 and DAP10 are important for lethal shock triggered by MDL-1.…”
Section: Activation Of Dap12 Dap10 Syk Pi3k and Akt Is Important mentioning
confidence: 66%
“…DAP12 has no extracellular domain and interacts with CLEC5A through an ionic interaction between polar residues in the transmembrane regions of both proteins (a lysine in CLEC5A and an aspartate in DAP12). The presence of this transmembrane ionic interaction has been shown to be critical for both DAP12 and DAP10 signaling (4,7,34). However, it is unclear how this charge-mediated association within the membrane could transmit information about ligand binding from the extracellular domain of CLEC5A to the intracellular signaling domain of DAP12 as there are no structural studies of the transmembrane interactions of DAP12 or DAP10 with CLEC5A.…”
Section: Clec5a Displays Conformational Flexibility-recombinantmentioning
confidence: 99%
“…An alternative structure is observed in 1 ⁄ 5 of the simulations where a distinct right-handed CLEC5A-DAP12 heterodimer forms through the same triad of residues but by interacting via an alternative face. In the light of the recent data suggesting a possible CLEC5A-DAP12-DAP10 interaction in osteoclasts, this alternative structure may represent a binding mode that accommodates an additional DAP10 helix (7). Such a structure would represent a right-handed CLEC5A-DAP12-DAP10 heterotrimer, which insulates the polar residues from the hydrophobic core of the membrane.…”
Section: Clec5a Displays Conformational Flexibility-recombinantmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that this receptor plays a crucial role in the pathophysiology of dengue virus infection, being directly involved in the production of proinflammatory cytokines by infected macrophages (Chen et www.intechopen.com Watson et al, 2011). CLEC5A has a very short cytoplasmic region lacking a defined signaling motif, yet it transduces intracellular signals trough non-covalent association with the ITAM-bearing adapters DAP10 and DAP12 (Bakker et al, 1999;Inui et al, 2009). DAP10 ITAM motif contains a cytoplasmic sequence that facilitates PI3K recruitment and activation, being possible that it cooperates with DAP12-associated receptors to mediate costimulatory signals (Kerrigan & Brown, 2010).…”
Section: Clec5amentioning
confidence: 99%